Child maltreatment and protection in the Arab Gulf Cooperation Council countries: A scoping review. (December 2022) - Neville, Sarah Elizabeth; Zidan, Tarek; Williams, Adam; Rotabi-Casares, Karen Smith
Abstract: Background: Research on child maltreatment and protection in the Arab Gulf Cooperation Council countries—Bahrain, Kuwait, Oman, Qatar, Saudi Arabia, and the United Arab Emirates (UAE)—is limited but growing, as is child protection as a sector. Objectives: We aimed to identify themes and gaps in existing research on child maltreatment and protection, identify opportunities for building capacity in research and practice. Participants and setting: N/A. Methods: We conducted a scoping review of empirical studies published in peer-reviewed journals in English and Arabic and reported methods and findings according to the PRISMA-ScR reporting protocol. Articles were coded by country, topic of research, and type of abuse studied, if any. Results: Our database search returned 6109 articles and 160 articles were included in our review. Themes included (1) prevalence, incidence, and characteristics of maltreatment, (2) outcomes associated with maltreatment, (3) attitudes, awareness, and reporting, (4) accidental injury and death potentially associated with neglect, (5) policy and practice. Eighty-seven articles studied Saudi Arabia, while 28 studied the UAE, 21 Kuwait, 13 Qatar, 12 Oman, and 11 Bahrain. Physical abuse was studied in 77 articles, followed by sexual abuse in 54 articles and emotional abuse in 54. Conclusion: Although the medical community produces an encouraging volume of child maltreatment research, gaps remain. Intervention research is lacking, and further inquiry into family dynamics, culture, and spirituality could inform the development of effective interventions. Cross-sectoral collaboration among education, social work, law enforcement, and healthcare is also needed to safeguard children's rights in the GCC. Highlights: Saudi Arabia has produced much of the research on child maltreatment and protection in the Arab Gulf region. Studies examined physical abuse most frequently. The same number of articles studied sexual abuse as emotional abuse. More intervention and prevention research is needed in order to safeguard child rights in the region.